Effect of Two-Stage Water Addition on Consistency of Processed Cheese: Physicochemical, Mechanical, Thermal, and Organoleptic Approach - Vincová, Anna; Polášková, Martina; Stěnička, Martin; Šantová, Kristýna; Kůrová, Vendula; Lapčíková, Barbora; Gryger, Tomáš; Lorencová, Eva; Lazárková, Zuzana; Pluta-Kubica, Agnieszka; Pětová, Markéta; Novosad, Ondřej; et al. (Foods (Basel, Switzerland), 2025)
The current study investigated the impact of two-stage water addition on the selected properties of processed cheese (PC). In particular, the above-mentioned novel approach involved adding water in two stages during the PC manufacturing process. The effects of this process on the physicochemical, viscoelastic, textural, tribological, thermal, and organoleptic properties of PC were evaluated. For all examined PC samples, the elastic modulus consistently dominated over the viscous modulus (G' > G″) across the entire frequency range. Moreover, it was observed that a smaller amount of initial water addition during the melting process resulted in a slight increase in the values of both viscoelastic moduli. The control sample exhibited the lowest lightness values, while it also showed the highest level of yellow coloring, suggesting that the two-stage addition of water affected the color of the PC samples. The results showed that the two-stage addition of water significantly influenced the physicochemical, viscoelastic, textural, tribological, thermal, and organoleptic properties of PC, leading to a modified texture, and thermal stability. Moreover, firmer PC products were obtained when a greater initial water level (first dosage; in the range of 60 to 90%) was utilized. This study could provide valuable information on the development of high-quality PC products with tailored functional properties, which can be important for the dairy industry.
Keywords: processed cheese; viscoelastic properties; tribological properties; textural properties; water addition; thermal properties